Verification of a Lagrangian particle model for short-range firebrand transport. (July 2017) - Wadhwani, Rahul; Sutherland, Duncan; Ooi, Andrew; Moinuddin, Khalid; Thorpe, Graham
Abstract: Firebrands are a harbinger of damage to infrastructure; their effects cause a particularly important threat to people living within the wildland-urban-interface. Short-range firebrands travel with the wind with little or no lofting, and cause spotfires. In this work, the design of a novel firebrand generator prototype is discussed to achieve a uniform shower of firebrands. The transport of short-range firebrand is studied to verify the existing Lagrangian particle model of Fire Dynamics Simulator. Uniform, non-combusting cubiform and cylindrical firebrands are projected using the firebrand generator. The experimentally observed distribution of particles on the ground is compared with a simulated distribution using the fire dynamic simulator. The results show that the existing Lagrangian model gives a good agreement with the experimental data.